FUNCTIONS AND METHODS OF USING COLORONYMS IN LITERARY TEXTS - D. M. Khayitova (Modern American Journals, 2025)
This article examines the semantic and stylistic functions of color terms in literary texts. The extent to which color names are widely used in artistic discourse and the mechanisms of their impact are analyzed on the reader, as well as the dependence of colors on cultural and social factors.
Keywords: coloronyms, literary text, semantics, stylistic feature, possibilities of language expression, figurative meaning, anthropocentric approach, cognitive approach, cultural context.